PENGARUH PENERAPAN METODE PEMBELAJARAN ACTIVE LEARNING TYPE TEAM QUIZ TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMAN O1 PAGUYAMAN PANTAI KABUPATEN BOALEMO - Thaib, Sri Apriani; Bumulo, Frahmawati; Ardiansyah, Ardiansyah; Bahsoan, Agil; Dama, Maya Novrita (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Low student achievement in Economics is often attributed to the use of teacher-centered instructional methods that do not optimally engage students in the learning process. Therefore, the implementation of learning methods that encourage active participation and collaboration among students is necessary. This study aims to examine the effect of the Active Learning method of the Team Quiz type on the Economics learning outcomes of tenth-grade students at SMAN 01 Paguyaman Pantai, Boalemo Regency. This research employed a quantitative approach with a quasi-experimental design. The research sample consisted of 58 students selected using purposive sampling techniques. Data were collected through questionnaires and documentation of learning outcomes and analyzed using SPSS software. The results indicate that the implementation of the Active Learning Team Quiz method has a positive and significant effect on students’ learning outcomes. Learning activities that emphasize group work, discussions, and team-based quizzes were found to enhance student engagement and improve their understanding of Economics concepts. Overall, the Team Quiz method proved to be effective in improving students’ learning outcomes. This study is expected to serve as a reference for teachers in applying active, collaborative, and student-centered learning strategies to enhance the quality of Economics instruction at the secondary school level.